Perceptions of Psychotherapy Trainees of Psychotherapy Research - Mark Widdowson (International Journal of Transactional Analysis Research, 2013)
The present study was conducted by the researcher to explore the perceptions and feelings that Transactional Analysis (TA) psychotherapy trainees had about psychotherapy research. The researcher was also preparing to conduct a practice research based project involving TA psychotherapists, and wanted to use the findings from the present study to inform the design of that project and anticipate and respond to the possible training and support needs of participants.